Galectin-3 expression in hippocampal CA2 following transient forebrain ischemia and its inhibition by hypothermia or antiapoptotic agents. Issue 5 (23rd March 2016) - Hisamatsu, Kenji; Niwa, Masayuki; Kobayashi, Kazuhiro; Miyazaki, Tatsuhiko; Hirata, Akihiro; Hatano, Yuichiro; Tomita, Hiroyuki; Hara, Akira
Abstract : Recent evidence has suggested that the hippocampal CA2 region plays an important role in the recognition process. We have reported that ischemic damage in the hippocampal CA2 region following transient ischemia is caused by apoptosis, but the underlying mechanisms are still not clear. Galectin-3 is a β-galactosidase-binding lectin that is important in cell proliferation and apoptotic regulation. We have also reported that galectin-3 was expressed in activated microglia in the CA1 region 96 h after transient ischemia. The aim of this study is to determine the localization and time course of galectin-3 expression in the CA2 region following transient forebrain ischemia. Galectin-3 immunostaining was observed in both interior side of CA1 region and CA2 region in hippocampus 60 h after ischemic insult. At 66 h, galectin-3 was observed in the whole CA1 region adjacent to the CA2 region in the hippocampus. Both galectin-3 expression and neuronal cell death in the CA2 region were significantly inhibited by hypothermia and by apoptosis-inhibiting reagents. These results suggest that galectin-3 in the CA2 region is expressed independent of that in the CA1 region. Protection of the expression of galectin-3 in the CA2 region might contribute toward the survival of CA2 pyramidal neurons.